Spore morphology and ornamentation in the genus Blechnum (Blechnaceae) - Passarelli, Lilian M. (2010)
A study of the spores of 64 neotropical and palaeotropical taxa of the genus Blechnum was performed using scanning electron microscopy (SEM). Two basic types of perispores were recognised: perispore smooth or only slightly ornamented (laevigate, with micro-granules or micro-lamellae, venulose and rugulate), and perispore ornamented (rugate, low reticulate, cristatereticulate, orbiculate, and colliculate). SEM observations allow for distinguishing differences in the structure of perispores, but the character does not correlate with the ornamentation. The smooth exospore predominates among the studied species. Results suggest that perispore characters have important diagnostic value, since different combinations of ornamentation/structure were found among the studied species. Moreover, when spore characters are considered together with other morphological traits of the sporophytes and the habit of plants, ornamentation of spores becomes a useful complementary feature at the specific level. The results are discussed in light of the recent systematic studies and emphasise that any eventual subdivision of the genus Blechnum must include characters of the sporophyte as well as spore features to ensure a more robust classification than the previously proposed. The spores also show a significant affinity between Blechnum and other genera of Blechnaceae, which was also suggested by recent phylogenetic studies.